Síntese e caracterização de peneira molecular mesoporosa mcm-41 com níquel impregnadas e in situ - KLEIN, Karina Vitti (2008)
The new family mesoporosas molecular sieves, known as M41S, have been very studied since its discovery in 1992, with bigger prominence for MCM-41, that had its mesoporosa structure that allows ample applications in catalytic processes. In this work were studied two reactions conditions of preparation of the MCM-41 and three forms of nickel incorporation. In the synthesis of the MCM-41 the hidrotérmico treatment and in conditions was used surrounding, while in the incorporation, was used to impregnation of ions nickel and nanopartículas of nickel oxide, as well as the direct synthesis where the nickel was introduced in the structure of the MCM-41, during the synthesis. The gotten materials had been characterized by elementary nickel analysis, X-ray diffraction, nitrogen adsorption/desorption, FT-IR spectra, thermogravimetric analysis, thermoprogrammed reduction. The characterizations had indicated that it had the formation of the mesoporosa structure with periodic pore system, typical of the MCM-41, in both methods of synthesis, being able to be evidenced the biggest viability of the synthesis of the MCM-41 in the surrounding conditions. It can also be verified that it had nickel incorporation in all samples, independent of as this element was inserted. The introduced samples that had had nickel during the synthesis had presented greater excessively average diameter of pores in relation. After the characterization, the samples with nickel had been tested as in the reaction of conversion of carbon monoxide the high temperatures catalytic, known as HTS reaction, presenting activity.